Editorial: Giving Voice to Novice Teacher-Researchers - Melba Libia Cárdenas; Melba Libia Cárdenas (Profile Issues in Teachers' Professional Development, 2019)
Profile was created as a forum to bring to the forefront the attempts of practitioners in doing action research. This was also an initiative promoted by scholars from different Anglo speaking contexts, in some cases, with different names and definitions—teacher research, exploratory action research, and exploratory practice, among others. All of them, in one way or another, highlight the fact that teacher education and educational policies confer importance to integrate research to the teaching profession.